Controlled directionality in 3D printing of graphite-reinforced polymer composite with enhanced mechanical properties. (12th April 2023) - Das, Manojit; Mishra, Rajat; Das, Palash; Kashyap, Sunil Kumar; Panda, Sushanta Kumar; Mitra, Rahul; Owuor, Peter Samora; Arora, Amit; Tiwary, Chandra Sekhar
Abstract: In a 3D printed polymer composite, orientation of the reinforcement, distribution and porosity plays a major role in its mechanical properties. Here, we demonstrate a precisely control of the orientation of the reinforcement by varying different printing conditions such as nozzle diameter and flow rates. The experimental observation reveals a direct correlation between the directionality of reinforcement, porosity, and mechanical properties with printing conditions. Printed composites show an enhancement of ∼108% in tensile strength, ∼520% in toughness, and ∼188% in fracture strain as compared to film casting method. In addition, we use discrete element modeling and computational fluid dynamics numerical methodology to visualize the orientation of reinforcement inside the nozzle. The effects of controlled variables on the directionality of the reinforcement and process-property dependency are validated. These findings open new opportunities in further strengthening the mechanism by which additive manufacturing can be used to tailor the properties of polymer composites. Graphical abstract: Image 1 Highlights: Graphite-reinforced polymer composites were fabricated through the 3D Direct ink writing process (DIW). An investigation of the directionality of the reinforcement was studied that can be tuned by controlling the input variables. The effects of orientation angle on the mechanical properties have been correlated. A multi-linear regression model has been developed to establish a relation between input and output variables. Samples with enhanced mechanical properties can be 3D printed with better control on orientation of reinforcement.